CLASSROOM DISCOURSE: TEACHER STUDENTS INTERACTION AND GENDER PARTICIPATION IN PRIMARY SCIENCE EDUCATION - Munasprianto Ramli (Jurnal Harkat : Media Komunikasi Gender, 2020)
Abstract. The objective of this research is to explore teachers-students domination and gender participation during classroom interaction primary science. This research employed descriptive case study approach. I am focusing my study on twelve science lessons at year four of two primary schools in the Greater Jakarta. Data were gathered using classroom observations. I wrote a field note for each lesson and record the observation using video recorder. The data gathered then analyze using descriptive statistics and thematic analysis approach.  The study shows that students speak just as frequently as teachers during the talk. However, this is not the case for talk coverage as teachers dominate classroom talk during a science lesson. In terms of gender participation during classroom talk, there is no evidence of gender domination. The study shows that the domination of one gender in each of these classes is not caused by a gender stereotype, but rather is due to the teacher’s strategies in maintaining social interaction in their classes. Abstrak. Tujuan dari penelitian ini adalah untuk mengeksplorasi bagaimana dominasi guru-siswa serta  partisipasi gender saat interaksi dalam pembelajaran sains di sekoah dasar.Penelitian ini menggunakan pendekatan studi kasus deskriptif. Peneliti memfokuskan studi pada dua belas pelajaran sains di kelas empat dari dua sekolah dasar di bagian selatan kota Jakarta. Data dikumpulkan menggunakan observasi kelas. Peneliti menulis catatan lapangan untuk setiap pelajaran dan merekam kegiatan pembelajaran. Data yang terkumpul kemudian dianalisis menggunakan statistik deskriptif dan pendekatan analisis tematik. Hasil penelitian ini menunjukkan bahwa dari segi frekuensi, siswa dan guru mempunyai frekuensi pembicaraan yang hampir sama. Akan tetapi dari segi durasi, guru terlihat mendominasi percakapan. Dalam hal partisipasi gender selama pembicaraan di kelas, terlihat bahwa tidak ada bukti dominasi gender secara umum.. Adanya partisipasi gender dalam beberapa pertemuan  bukan disebabkan oleh stereotip jenis kelamin, tetapi lebih disebabkan oleh strategi guru dalam menjaga interaksi sosial di kelas mereka.